A MODEL OF FACTORS’ EFFECTS ON BRAND IDENTIFICATION: EVIDENCE FROM IRAN - Shahriar Azizi; Zahra Daei (Asian Academy of Management Journal, 2014)
Social identification is essentially a perception of oneness with a group of persons. This study designs a model that tests and identifies social factors affecting brand identification. A convenience sample of 383 visitors to Ala Eddin Market (Mobile Market in Tehran) was surveyed. A series of linear regressions to test the hypotheses were completed using Path Analysis. The results showed that brand trust and brand attractiveness have positive effects on brand identification. The results also revealed that ideal self-congruity, brand distinctiveness and brand attractiveness have positive effects on brand trust, which in turn indirectly influence brand identification. Ideal selfcongruity and brand distinctiveness also positively affect brand attractiveness, which indirectly influence brand identification. However, the findings of the study indicate that actual self-congruity has no significant effect on brand trust and brand attractiveness.